CROSSED TESTICULAR ECTOPIA; A CASE REPORT. - Muhammad Saifullah; Muhammad Tahir Bashir; Muhammad Akram Malik (Journal of University Medical & Dental College, 2018)
ABSTRACT: Crossed testicular ectopia is a rare anatomical anomaly in which both testis descend into the same hemiscrotum using the same inguinal canal. More than 100 cases have been reported in the literature up till now. Our patient was a 7 year old child who presented with the absent right testis and left incomplete inguinal hernia. While undergoing left inguinal exploration, a second testis with a hernia sac was identiﬁed at deep inguinal ring. Both testis had a separate blood supply. Herniotomy and ﬁxation of ectopic testis on the opposite side through a suprapubic subcutaneous tunnel was done. TTE should be suspected in patients with inguinal hernia having absent contralateral testis. Ultrasonography and laparoscopy can be helpful in pre-operative assessment of TTE. Long-term follow-up is recommended in all patients of TTE because of risk of malignant transformation and fertility concerns.